THE INFLUENCE OF DISTRIBUTION CHANNELS, PRODUCT AVAILABILITY, AND PRICE ON PURCHASING DECISIONS AT THE APONG CRICKET FARMING BUSINESS IN TEBING TINGGI CITY - Angge Lya; Aprilia Jennifer Lie; Rodi Syafrizal; Willy Cahyadi (CV. Radja Publika, 2026)
Increasingly intense business competition requires entrepreneurs to thoroughly understand the factors that drive consumers to make purchasing decisions. This study aimed to determine the extent to which distribution channels, product availability, and price influence consumer purchasing decisions at the Apong Cricket Farming Business in Tebing Tinggi City. A total of 96 respondents were involved in this research through an incidental sampling technique, with data collected via questionnaires and analyzed using multiple linear regression on SPSS version 25.In terms of individual influence, distribution channels and price proved to be significant, with significance values of 0.002 and 0.000, respectively, whereas product availability did not show a significant effect, with a value of 0.378. When tested simultaneously, the three variables collectively proved to significantly influence purchasing decisions, yielding a calculated F-value of 26.277 and a significance level of 0.000. Furthermore, the Adjusted R Square value of 0.444 implies that 44.4% of the variance in purchasing decisions can be explained by the three variables in this model. These results indicate that price stability and distribution effectiveness are the two main factors that micro-agribusiness entrepreneurs must consider when designing well-targeted marketing strategies.